Identifikasi Hubungan Variabel Indikator Ekonomi dengan Estimasi Biaya Proyek Konstruksi - Lydiawati Soelaiman; Basuki Anondho (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Contractors’ cost estimation has a very important effect in every company’s performance which will be needed in fulfilling every customer’s needs. Nevertheless, in order to minimize the inaccuracy between the estimated cost and actual performance, it will be better to accommodate the economic condition in terms of estimating. In all the developing countries such as in Indonesia, the economic condition is most likely to be unstable thus it will be influence to the accuracy of estimation. The purpose of this research is to find all the indicator economic variables which had been influenced so the project is able to be optimized. The result shows that money currency has a strong impact. In order to comprehend this information, data needs to be collected from central bank, newspapers, the expert, and also the estimator themselves.Keywords: Estimasi Biaya, Proyek Konstruksi, Pengaruh Indikator Ekonomi